THE DEVELOPMENT OF ELECTRONIC PORTFOLIO FOR AUTHENTIC ASSESSMENT ON COMPUTER EDUCATION PROJECT FOR UNDERGRADUATE STUDENTS AT COMPUTER EDUCATION DEPARTMENT, NAKHON PATHOM RAJABHAT UNIVERSITY - Thaiposri, Patamaporn (Journal of Education and Innovation, 2024)
The aims of this research study were: 1) to design an electronic portfolio for authentic assessment on Computer Education Project for undergraduate students at Computer Education Department, Nakhon Pathom Rajabhat University, 2) to develop an electronic portfolio, 3) to evaluate the efficiency of the electronic portfolio, and 4) to study student satisfaction regarding the use of the electronic portfolio. The sample group was 108 undergraduate students from the Computer Education Department, Faculty of Science and Technology, Nakhon Pathom Rajabhat University, who enrolled in the Computer Education Project course during the second semester of the 2021 academic year. They were selected using a simple random sampling method. The research instruments included 1) an electronic portfolio, 2) an efficiency evaluation form, and 3) a satisfaction questionnaire. Data were analyzed using mean ( ) and standard deviation (SD). The research findings were as follows: 1) the structure of the electronic portfolio was divided into three parts: 1.1) Introduction: this part showed the basic data of the project. 1.2) Content: this part showed the student tasks that were created at each phase of the project, and 1.3) Assessment: this part showed the criteria and the results of the assessment of the student task. 2) The electronic portfolio was developed in the form of a web application format. The students collected documents and evidence that related to the project. The advisor was able to track the progress, monitor, give some suggestions, and assess the student task using an authentic assessment process. 3) Overall, the experts agreed that the electronic portfolio displayed a very high level ( = 4.92, SD = 0.27) of efficiency, and 4) the students were satisfied at a very high level ( = 4.81, SD = 0.41) with regard to the use of the electronic portfolio.